A Pattern-Based Layout Algorithm for Diagram Editors - Maier, Sonja; Minas, Mark (Electronic Communications of the EASST, 2007)
The diagram editor generator framework DIAMETA utilizes meta-model-based language specifications and supports free-hand as well as structured editing. We presented a generic layout algorithm that meets the demands of this kind of editors. The algorithm combines two concepts, constraint satisfaction and attribute evaluation, to a powerful methodology for specifying the layout for a particular visual language. As the layout specification for this algorithm is rather complex, we encapsulated basic functionality into reusable patterns. This paper describes this pattern concept of the generic layout algorithm, and shows how they simplify the layout specification of a specific language.